2019
DOI: 10.1055/s-0038-1676352
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Evaluation of Surgical Wound Dressings and the Incidence of Surgical Site Infections in Dogs Undergoing a Tibial Plateau Levelling Osteotomy

Abstract: Objective The main aim of this study was to evaluate the efficacy of a topical 2-octyl cyanoacrylate (2OC) tissue adhesive and an adhesive barrier dressing (BD) in minimizing the incidence of surgical site infections (SSI) in dogs undergoing a tibial plateau levelling osteotomy (TPLO). Materials and Methods In a prospective clinical study, 437 client-owned dogs undergoing a TPLO as treatment for cranial cruciate ligament disease with or without concurrent patellar luxations from July 2015 to Septem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Previous studies have found SSI rates of 2.3%-25.9%, 2.6%-15.4%, 4.2–17.3%, and 2.2%-10.3% after tibial plateau leveling osteotomy (TPLO), tibial tuberosity advancement (TTA), lateral fabellar suture (LFS), and medial patellar luxation (MPL) correction surgeries, respectively [ 1 – 20 ]. Increased risks of surgical site infections have been found to be multifactorial, with increased risk found to be associated with age, weight, duration of anesthesia and surgery, among others [ 1 , 5 , 8 , 10 12 , 21 – 23 ]. Minimizing surgical site infection rates is important for optimal patient healing, improved client satisfaction, and reduction of additional client costs [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found SSI rates of 2.3%-25.9%, 2.6%-15.4%, 4.2–17.3%, and 2.2%-10.3% after tibial plateau leveling osteotomy (TPLO), tibial tuberosity advancement (TTA), lateral fabellar suture (LFS), and medial patellar luxation (MPL) correction surgeries, respectively [ 1 – 20 ]. Increased risks of surgical site infections have been found to be multifactorial, with increased risk found to be associated with age, weight, duration of anesthesia and surgery, among others [ 1 , 5 , 8 , 10 12 , 21 – 23 ]. Minimizing surgical site infection rates is important for optimal patient healing, improved client satisfaction, and reduction of additional client costs [ 24 ].…”
Section: Introductionmentioning
confidence: 99%